Effect of temperature on zirconia powder synthesized from amang zirconium oxychloride precursor / Nurul Asilah Md Amin ... [et al.] - Md Amin, Nurul Asilah; Subuki, Istikamah; Sapiee, Nurul Haiza; Kassim Shaari, Norin Zamiah (UiTM Press, 2024)
Silica (SiO2) is widely used in numerous applications, including ceramic membranes, and can be extracted from rice husks, which is an agricultural waste containing high amounts of silica. In fact, it is essential to reduce the vast amounts of discarded rice husks as open burning of the rice husk can have detrimental effects on the environment due to the release of hazardous pollutants. For the rice husk to be used, a suitable sintering temperature should be obtained to ensure the membrane synthesized has the desired porous structure. A high sintering temperature can affect the melting condition of the membrane’s porous structure. While a low sintering temperature may not give the required porosity. Therefore, this study aims to evaluate the effect of sintering temperature on the pore size of the membrane fabricated from kaolin, polyvinyl alcohol, and rice husk ash. The rice husk was initially treated with hydrochloric acid (HCl) and heated at 900 ℃ to produce rice husk ash. The membranes fabricated were then sintered at 1000 ℃ to 1400 ℃. X-ray fluorescence (XRF) results show that 71.36% of silica was successfully extracted from the rice husk. According to the XRD results, only two membranes sintered at 1300 °C and 1400 °C have crystallinity forms. Because the ceramic membrane contains a crystalline phase, it was determined that 1300 °C is an appropriate temperature for sintering. It also has a low absorption percentage (88.89%) and the desired porosity (69.93%).